2001
DOI: 10.2308/aud.2001.20.2.85
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Judgments of New Clients' Integrity upon Risk Judgments, Audit Evidence, and Fees

Abstract: Client integrity concerns auditors when they plan new audit engagements because it is related to both fraud risk and the source credibility of clients. Auditors may increase audit work and fees when they judge integrity to be below normal. In an experiment, a sample of 63 Canadian audit partners read information about a prospective audit client, including information about the client's CFO. This information was manipulated to support a judgment of either high or low integrity. As hypothesized, judgments of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 23 publications
2
66
0
1
Order By: Relevance
“…Beaulieu (2001) found evidence of a negative relationship between perceived client integrity and audit effort. Kizirian et al (2005) found that management integrity impacts risk assessments and corresponding audit scope.…”
Section: Fraud Attitude and Auditor Fraud Risk Assessmentsmentioning
confidence: 97%
“…Beaulieu (2001) found evidence of a negative relationship between perceived client integrity and audit effort. Kizirian et al (2005) found that management integrity impacts risk assessments and corresponding audit scope.…”
Section: Fraud Attitude and Auditor Fraud Risk Assessmentsmentioning
confidence: 97%
“…The auditor applies multiple heuristics in evaluating the sufficiency and appropriateness of audit evidence, paying special attention to the source credibility of the information (Hirst 1994a, 113). Such attention to the source of information is in line with the regulatory guidance (e.g., AICPA 2006a, 2006b) and findings of prior research, which documents the discounted influence of information from non-credible sources on a variety of decisions in the accounting domain (e.g., Beach et al 1978;Beaulieu 1994Beaulieu , 2001). …”
Section: Prior Research and Hypothesesmentioning
confidence: 59%
“…When auditors face low credibility management, ceteris paribus, auditors increase audit effort by collecting more persuasive evidence and looking for additional sources of evidence outside management control (Beaulieu 2001;Kizirian et al 2005).…”
Section: Prior Research and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rose (2007) found that less trusting auditors were more likely to be skeptical about perceived evidence of aggressive reporting. Goodwin (1999) found that auditors' sensitivity to client integrity (i.e., the trust an auditor has in their client) affected auditors' decision such as assessments of audit risk (Ponemon & Gabhart, 1993;Beaulieu, 2001). (Note 3) While Krambia- Kapardis (2002) found that client integrity was significant with respect to perceptions of the relevance of the information, Kizirian Mayhew, and Sneathen (2005) found that auditors required more persuasive audit evidence (i.e., more external information) when management integrity was perceived as being low (i.e., auditors' did not trust the client).…”
Section: Trust: An Overviewmentioning
confidence: 99%